FEMINIST AGENDA: PAUL’S VIEW OF WOMEN IN 1 CORINTHIANS 11: 2 – 16 - Odewole, Israel O.O. (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2025)
Apostle Paul’s view of women in 1 Cor. 11:2-16 has generated strong debate among scholars and theologians over the years. Many have tried to do an exegesis of this passage along the theme of the ‘Feminist Agenda’. Furthermore, there has been lot of 21st century cultural prejudices thereby side-lining the cultural milieu in which Paul wrote. This paper will examine 1 Cor. 11:12-16 in the light of the ‘Feminist agenda’ which has generated much heated debates even from both male and female sexes. Male chauvinists has always argued against inequality of both sexes with the female been subjugated. It becomes more worrisome if their argument is justified using the scriptures. The Church of ages has tried to solve the problems of men and women through a ministry composed exclusively of men. This is no more adequate to redeeming the world at present than an exclusively feminine ministry would be. Feminist’s voices and other similar ones will set the tone of this presentation which, simply indicate that there is a cry for “women approach” to their own affairs which must be articulated, controlled and sustained by them. It is against such a mood that I make this contribution by looking deeply to the passage in order to make suggestions and recommendation for modern churches.